THE UNIQUENESS OF MAN IN THE LIGHT OF THE BIBLICAL CONCEPTION - SAHAIDACHNA, SOFIIA (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
Man is the crown of God’s creation. And his exclusivity with regard to other creatures is clearly defined by the biblical concept. This article includes an explanation of man’s place in the Bible, also in God’s plan of creation and in his mission and destiny in the world.